Use of soft waste of the Peruvian scallops Argopecten purpuratus (Lamarck, 1819) to produce high protein meal - Colán-Ramos, Claudio (2019)
The scallop soft waste obtained during processing is discarded, generating environmental liabilities to the mariculture industry in Peru. However, these residues constitute a potential raw material to produce meal for balanced feeds. In this sense, a methodology was developed for the elaboration of meal from the soft residues of the Peruvian scallop. The product obtained had a composition of 61% protein, 7.5% fat and 11.7% moisture. The development of technologies that allow the processing of large volumes of waste could contribute to the more efficient and profitable use of this raw material.